Take control! insights into irritable bowel syndrome - Dancey, Christine P.; Rutter, Claire L. (Tfm Pub., 2005)
Different from other IBS self-help books - approaches coping with IBS using concepts and skills based on the individual's own psychological profile. Shows how a greater knowledge of IBS - especially its psychological and social factors - can lead to a reduction in feelings of being stigmatized and depressed, to a feeling of greater well-being. Complex psychological constructs are explained simply and with the aid of examples and real-life vignettes taken from case studies.